O consumo da corrida de rua e seus significados - Titton, Laís Ruiz Fuchs (2017)
The consumption of products and services, besides providing physical and biological needs, also concern symbolic functions for the consumers, both representing important tools to marketing professionals formulate their strategies. This dissertation aimed to understand and compare the consumption and the meanings of running as an amateur sport modality practiced individually and in group. The theoretical background was based on consumer behavior research that embraces the meanings of consumption. In order to develop this study, a qualitative and descriptive study with a sectional cut was carried out, guided by the necessity to make an in depth investigation. Data collection was performed through nonparticipant observation and interviews with 22 amateur runners current living in Maringá-PR. Data analysis was performed through content analysis involving the Atlas.ti software. With respect to the main meanings attributed to running, they are: Overcoming; Well-being; Socialization; Challenge; Freedom; Passion; Addiction and Pleasure. Furthermore, it was possible to notice a higher identification of individual runners to the meanings related to Freedom, Well-being and Challenge, and for group runners a higher valorization of Overcoming and Socialization. The results showed five categories of products and services consumed by amateur runners: food and supplements; clothing; accessories; personal care and services. This study contributes theoretically to the meanings attributed to running and explores the influence of the categories of cultural meanings in the consumer behavior of individual and group runners. As managerial contributions, it is suggested higher investments in communicating the products and services to runners, whereas they are little known and consumed, exploring the meanings raised by this study. The main limitations of the study were deepening a few interviews with male participants, and the lack of interviewees above 55 years old. For future research, it is suggested the investigation of different agents that operate in the runners market, such as creators and developers of products, distributors and retailers.